FIKIH MODERAT DAN VISI KEILMUAN SYARI’AH DI ERA GLOBAL - Nashiruddin, Muh. (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2016)
This paper examines the jurisprudence moderate in a global context. Focus of this study is not only theoretical but also practical studies examined by the two principal sub study, the concept of jurisprudence moderate epistemological argument as a scientific vision of the Faculty of Sharia IAIN Surakarta in the global era and moderate form of implementation of the concept of jurisprudence as a scientific vision of the Faculty of Sharia IAIN Surakarta in the global era. By using descriptive-qualitative research and content analysis method (content analysis), the study concluded that moderate jurisprudence is the integration effort between a literal understanding of the text and maqasid ash-Shari'ah, which is to understand the balance between as-sawabit and almutaghayyir, between the literal understanding with liberal notions become a necessity today. Faculty of Shariah IAIN Surakarta have not a vision of science and fiqh clear patterns of thought so that there are no policies related to vision science and also patterns of thought jurisprudence at the Faculty of Sharia IAIN Surakarta. Jurisprudence existing patterns of thought is highly dependent on the mode of thinking that administer the course lecturers.